ASSESSMENT OF URBAN GENERATED CLIMATE ANOMALY IN OKENE TOWN, OKENE LOCAL GOVERNMENT AREA OF KOGI STATE, NIGERIA: None - Sunday, Ishaya (FUDMA JOURNAL OF SCIENCES, 2020)
Abstract This study assessed urban generate climate change in Okene town of Kogi State, Nigeria. The objectives of this study include acquiring temperature, relative humidity and solar radiation data from SWAT satellite image from 1986 to 2016; determine the trend, normality, changes in temperature, relative humidity and solar radiation in the study area from 1986 to 2016. Climate data was collected from the Soil and Water Assessment Tools (SWAT) from 1986 to 2016 of Okene Town. Simple Statistical Measures of mean, maximum, minimum, standard deviation, Average deviation, coefficient of variation, skewness and kurtosis were used for discerning the trends and normality of temperature, relative humidity and solar radiation. The chi square statistical test was use to test the study hypothesis. The trend line equation shows positive for temperature (0.0567x +26.27), Solar radiation (0.036x + 18.1) and negative trend in relative humidity (y = -0.001x + 0.733). Chi square statistical result shows that there are significant changes in temperature, relative humidity and solar radiation over the past three decades in Okene town of Kogi State. In tackling this anomaly, there is need for greening the town by embanking on radical planting of trees and creation of cool pavement technologies towards cooler surfaces by convection or higher reflectance as adaptive/mitigation measures against Urban Heat Island in Okene town.